Stress response and contact behavior of PEMFC during the assembly and working condition. (26th August 2021) - Zhang, Jie; Hu, Yang; Han, Chuanjun; Zhang, Han
Abstract: Mechanical behavior of proton exchange membrane fuel cell (PEMFC) is closely related to its service life. Stress response and contact behavior of PEMFC during the assembly and working condition were investigated. Effects of clamping force, steel bands number and width on the mechanical behavior of PEMFC were discussed. Thermal-mechanical coupling was considered during the PEMFC working for thermal effect caused by chemical reaction. The results show that stress distribution of multi-cells is more uniform after assembly. Stress and contact pressure distributions of single-cell and multi-cells are similar after assembly. During the assembly process, the average contact pressure between the MEA and other parts increases with the increasing of clamping force, steel band width and number. With the steel bandwidth increases, the contact pressure distribution of MEA is more uniform. And the chemical reaction inside the fuel cell is more favorable. Stress concentration is prone to appear on the corners of GDL on the MEA, corners of sealing gasket, and edges of bipolar plate ribs, which may cause seal failure after long-term work. Under working condition, thermal expansion can enhance the sealing performance, but affect stress of bipolar plate and MEA. Those results can be used for design, manufacturing, maintenance and evaluation of PEMFC. Highlights: Mechanical behavior of PEMFC during assembly and working were investigated. Stress distributions of single and multi-cells are similar after assembly. Contact pressure increases with clamping force, steel band width and number. Stress concentration appears on corners of GDL and sealing gasket. Thermal expansion can enhance sealing performance during working condition.